Lung Preservation With Perfadex or Celsior in Clinical Transplantation: A Retrospective Single-Center Analysis of Outcomes. Issue 9 (September 2015) - Gohrbandt, Bernhard; Simon, Andre R.; Warnecke, Gregor; Fischer, Stefan; Hagl, Christian; Niehaus, Adelheid; Gottlieb, Jens; Welte, Tobias; Haverich, Axel; Strueber, Martin
Abstract : Background: Despite improvement of lung preservation by the introduction of low-potassium dextran (LPD) solution, ischemia-reperfusion injury remains a major contributor to early post-lung transplant graft dysfunction and mortality. After favorable experimental data, Celsior solution was used in our clinical lung transplant program. Data were compared with our historic LPD cohort. Methods: Between January 2002 and January 2005, 209 consecutive lung transplantations were performed with LPD. These were compared to 208 transplants between February 2005 and September 2007 with Celsior. Endpoints included posttransplant PaO2 /FiO2 ratio at different timepoints after intensive care unit (ICU) admission, posttransplant ventilation time, ICU stay and 30-day mortality, follow-up survival, and bronchiolitis obliterans syndrome-free survival. Results: Ratios of sex, urgency status, type of procedure, length of posttransplant ICU stay, and age did not show significant differences between the 2 groups. Mean ischemia times were significantly longer in the Celsior group (LPD, 355 ± 105 minutes vs Celsior, 436 ± 139 minutes, P < 0.001). Overall 3-year-survival (LPD, 66.5% vs Celsior, 72.0%; P = 0.25) was nonsignificantly improved in the Celsior cohort. Conclusions: A trend toward better survival ( P = 0.09) and increased freedom from bronchiolitis obliterans syndrome ( P = 0.03) was observed in the Celsior group despite prolonged ischemic times compared with LPD. Lung preservation with Celsior is safe and effective and may carry advantages. Abstract : Preservation of lung allografts has been investigated using Celsior solution in a single-center study and compared to a historical cohort of low-potassium dextran preserved lungs. The study of 417 patients shows longer ischemia times in the Celsior group, increased freedom from BOS and equivalent survival rates. Supplemental digital content is available in the text.